Sosialisasi Efek Penggunaan Alat Bantu Tenis Lapangan - Dwi Hartanto; Utami Dewi; Abdillah; Mira Fuzita; Anang Qosim (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The aim to be achieved through this tennis tool socialization activity is to provide insight for teachers in preparing learning media, especially for tennis subjects, and also for students with the tools to motivate students to do more, and no less important, the learning process does not cause boredom. for students to perform punching movements. The targets of this activity are teachers and students at SMP N 1 Segedong. This dedication will be carried out in September 2023. The tennis aids have been made and are ready to be used on the court. The final result is that it is hoped that with the socialization of the tennis stone tool, it can improve the results of good tennis shots, both forhend and backhand, in students. Meanwhile, for teachers, it is hoped that it can become an innovative alternative learning media so that it can motivate students to learn.